Multidrug resistant verocytotoxin-producing Escherichia coli O157:H7 in the faeces of diarrhoeic and non-diarrhoeic dogs in Abeokuta, Nigeria (2014)
Verocytotoxin-producing Escherichia coli (VTEC) 0157:H7 is a predominant cause of haemorrhagic colitis (HC) and haemolytic uraemic syndrome (HUS) in humans. To assess thè role of dogs as a possible source oftransmission ofVTEC 0157:H7 to humans, thè faeces of diarrhoeic (31) and non-diarrhoeic (63) dogs were examined for thè presence of thè organista. Escherichia coli 0157:H7 was isolated from 22 (23.4%) out of 94 samples examined. The organism was detected in 5 (16.1%) out of 31 diarrhoeic faeces and 17 (26.9%) out of 63 non-diarrhoeic faeces, but thè difference was not statistically significant (P>0.05). All thè E. coli 0157:H7 isolates produced one or both of verocytotoxin 1 and 2 (VT1 and VT2). Verocytotoxin 1 (VT1) was detected in 10 (45.5%) out of 22 isolates, VT2 in 8 (36.4%), while both toxin types were detected in four (18.2%) isolates. Sixteen (72.7%) out of 22 isolates were resistant to at least three antimicrobials from different classes, while 18 distinct antimicrobial resistance pattems were observed among thè isolates. The isolates showed resistance to ampicillin (86.4%), chloramphenicol (36.4%), ciprofloxacin (4.5%), gentamicin (18.2%), kanamycin (68.2%), nalidixic acid (22.7%), neomycin (40.9%), norfloxacin (9.1%), streptomycin (63.6%), sulphamethoxazole/ trimethoprim (63.6%) and tetracycline (77.3%). The present study showed that diarrhoeic and non-diarrhoeic dogs may serve as potential sources of multi-drug resistant VTEC 0157 :H7 transmissible to humans.